PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA TENTANG MATERI SUMBER ENERGI DI KELAS IV SDK RABASA - Nenometa, Natalia Luruk; Manafe, Yetursance Y.; Banu, Adam Bol Nifu (Journal of Character and ELementary Education, 2024)
The aim of this research is to determine the application of the discovery learning model to improve students' science learning outcomes regarding energy sources in class IV at Rabasa Catholic Elementary School, Malaka Regency. This research is a type of classroom action research (PTK) with stages including planning, implementation, observation, and reflection. This research was carried out in II cycles. The research location was Rabasa Catholic Elementary School with the research subjects being class IV students with a total of 13 students. The data collection techniques used in this research are observation, tests, and documentation. Based on the research results, it was concluded that student learning outcomes had increased after implementing the discovery learning model in science subjects on energy sources. This can be seen in the first cycle of student learning results, which showed that students completed their learning with a percentage of 46.15% with the number of students who completed it being 6 people. Meanwhile, in cycle II, student learning outcomes were completed with a percentage of 92.30% with 12 people completing the study. From cycle I to cycle II there was an increase of 46.15%. In this way, this classroom action research was successful, so the researchers stated that the application of the discovery learning model could improve student learning outcomes in science subjects on energy sources